FAK controls the mechanical activation of YAP, a transcriptional regulator required for durotaxis. Issue 2 (3rd January 2018) - Lachowski, Dariusz; Cortes, Ernesto; Robinson, Benjamin; Rice, Alistair; Rombouts, Krista; Del Río Hernández, Armando E.
Abstract : Focal adhesion kinase (FAK) is a key molecule in focal adhesions and regulates fundamental processes in cells such as growth, survival, and migration. FAK is one of the first molecules recruited to focal adhesions in response to external mechanical stimuli and therefore is a pivotal mediator of cell mechanosignaling, and relays these stimuli to other mechanotransducers within the cytoplasm. Yes‐associated protein (YAP) has been identified recently as one of these core mechanotransducers. YAP translocates to the nucleus following changes in cell mechanics to promote the expression of genes implicated in motility, apoptosis, proliferation, and organ growth. Here, we show that FAK controls the nuclear translocation and activation of YAP in response to mechanical activation and submit that the YAP‐dependent process of durotaxis requires a cell with an asymmetric distribution of active and inactive FAK molecules.—Lachowski, D., Cortes, E., Robinson, B., Rice, A., Rombouts, K., Del Río Hernández, A. E. FAK controls the mechanical activation of YAP, a transcriptional regulator required for durotaxis. FASEB J. 32, 1099–1107 (2018). www.fasebj.org